Bismuth-based Erbium-doped fiber for mode-locking and nonlinear applications / Mohammadreza Abdolhosseini Moghaddam - Moghaddam, Mohammadreza Abdolhosseini (2012)
Nature of Bi-related emission centers is not yet clear. Further research must be conducted to have a broadband low noise amplification and to raise efficiencies to level exhibited by silica-EDF systems. The pulse duration in generated train of pulses is one order of magnitude lower than that of a typical EDFA.This thesis describes laser generation process based on nonlinear effects, utilizing highly nonlinear fibers or/and Bismuth-based Erbium Doped Fiber (Bi-EDF). Various configurations were demonstrated using the Bi-EDF to generate various seed signals for optical amplifiers and nonlinear applications. Nonlinear effects both through stimulated Brillouin Scattering and slicing of spectrum were used to generate ultra wide multiwavelength comb lines or tunable narrow linewidth signals. A high-power double-clad amplifier was theoretically analyzed and experimentally used for both ultra-narrow linewidth and ultra short pulsed signals to provide the highest and flattest possible gain in the 1545-1566 nm wavelength regions. A maximum output power of 400 mW with a laser linewidth of less than 1 KHz was obtained in narrow linewidth operation. The construction of a low threshold mode-locked laser with an energy fluctuation of less than 2.5%. was successfully accomplished and supercontinuum (SC) in different types of fibers, was also studied. Although Bi-EDF devices have previously been used to amplify and generate pulses of light in the picosecond domain, this is the first time ultrashort pulses have been achieved in the femtosecond domain without using any intra-cavity or extra cavity compressors. The pulse width can continuously vary from 1.2 ps to 131 fs. In addition, the variations of the spectral width, time-bandwidth products, pulse duration, amplitude and timing jitters as a function of the pump power were also investigated for various output ports at various regimes. The pulses were then amplified at different power and injected into fibers with various dispersion profiles. The results show a considerably flat spectrum covering 500 nm to about 2.2 μm in dispersion flattened highly nonlinear fiber. A temperature sensitive loop mirror (TSLM) was proposed for slicing of spectra. Compared to conventional schemes, experimental results show that by using our proposed TSLM, one can potentially achieve a substantial improvement (6.6 times more) in increasing spectral spacing variation range and a considerable increment (337.6%) in temperature sensitivity.